Characteristics of protein‐based biopolymer and its application. Issue 3 (9th May 2014) - Gupta, Pratima; Nayak, Kush Kumar
<x xml:space="preserve">Abstract</x> This article aims to review the present scenario of protein based natural polymer development, which has the ability to stand against synthetic polymer. Demand of natural polymers would increase in future considering their environmental safety aspect. Protein characteristics and their suitability for polymer development are discussed here, along with the polymer reinforcement techniques such as development of blends, chemical block copolymerization, and modification of existing protein material, which are used for the development of biopolymer from protein. The application of protein based polymer product range varies from food and nonfood packaging stuffs to healthcare sectors. POLYM. ENG. SCI., 55:485–498, 2015. © 2014 Society of Plastics Engineers